Effect of Bicarbonate Salts and Sequential Using of Frying Oil on Acrylamide and 5-Hydroxymethylfurfural Contents in Coated Fried Chicken Meat - Aykin, Elif; Arslan, Sultan; Durak, Atike N.; Erbas, Mustafa (Taylor & Francis Inc, 2016)
In this research, the effect of different bicarbonate salts (sodium and ammonium) and their doses (0, 1, 2, and 3 g/100 g raw material) in the coating batter formula use and the sequential use of frying oil (1st, 2nd, 3rd, and 4th) on 5-hydroxymethylfurfural and acrylamide contents in coated fried chicken meat. The addition of sodium bicarbonate was efficient for reducing acrylamide content, but it increased browning and 5-hydroxymethylfurfural content compared to the control. When increasing the doses of sodium and ammonium bicarbonate from 1 to 3 g/100 g of raw material, the acrylamide content of samples did not change significantly, although adding sodium bicarbonate significantly reduced the acrylamide content as a control. These research results showed that using about 1 g/100 g raw material sodium bicarbonate rather than ammonium bicarbonate and as little frying oil as possible use during the production of coated and fried meat results in lower contents of 5-hydroxymethylfurfural and acrylamide.
Keywords: Coated meat; Bicarbonate salts; Maillard reaction; HMF; Acrylamide